Effect of Black Ear Mushroom Substitution on Organoleptic, Physical, and Chemical Characteristics of Chicken Nugget - Isro' Fajar Masitoh; Octavianti Paramita (Universitas Negeri Padang, 2026)
This study aims to determine the effect of black ear mushroom substitution on organoleptic quality including sensory quality (taste, aroma, texture) and hedonic preference (color, taste, aroma, texture, overall), physical quality on color parameters, and chemical quality which including moisture content, protein, and fat content of chicken nuggets. The study was conducted by an experimental method with a completely randomized design (CRD) consisting of three treatments: P1 = 0% black ear mushroom substitution, P2 = 20% black ear mushroom substitution and P3 = 40% black ear mushroom substitution. The research was conducted from December 11, 2025 to February 4, 2026, and data collection was carried out at the Pastry Laboratory, Culinary Education Study Program, Universitas Negeri Semarang. The study involved 3 expert panelists for sensory testing and 80 untrained panelists for preference sensory testing, using a likert scale of 1-9. Organoleptic and chemical quality data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test, preference data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test. Furthermore, the physical quality of the color parameter was analyzed descriptively using a digital imaging method based on the CIE (L*a*b*) color system. The result showed that black ear mushroom substitution up to 40% did not result in significant differences in sensory attributes, including taste, aroma, and texture. However, the substitution had a significant effect on panelist’s preference for color, taste, aroma, texture and overall acceptance. Descriptive analysis of the color parameter indicated that the substitution of black ear mushroom did not result in noticeable color changes on either the external and internal parts of chicken nuggets. Chemical quality analysis revealed significant differences in moisture, protein, and fat contents. The 20% substitution treatment (P2) showed the best balance with moisture content of 53.39%, protein content of 26.00%, and fat content of 18.83%, and was most preferred by panelists with an overall acceptability score of 8.08±0.67